A discourse analysis of news reports on climate change in english and vietnamese (2025)
There is growing concern over climate change all over the world, especially, when climate change currently causes a lot of disasters such as floods, drought… Therefore, how to write articles effectively, especially articles on climate change should be paid considerable attention to. The study aims at analyzing the typical discourse features of news reports on climate change in English and Vietnamese as well as discovering similarities and differences between the two languages in terms of layout, syntactic features, lexical choice and cohesive devices. There were five methods used in this thesis: Qualitative and quantitative methods, statistic and descriptive methods, analytic and synthetic methods, comparative and contrastive methods, inductive method. There were 60 samples of news reports on climate change (30 in English and 30 in Vietnamese), collected from the internet for analysis. The findings show that news reports on climate change in English and Vietnamese employ a variety of syntactic features such as simple sentences, compound sentences, a complex sentence, a compound-complex sentence, comparative construction. Besides, reference, ellipsis, conjunction and repetition in both English and Vietnamese news reports were also exploited in cohesive devices.